2005
DOI: 10.1016/j.tranpol.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Wedded to the car: women, employment and the importance of private transport

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.) Wedded to the car: women, employment and the importance of private transport Lynn DobbsThis paper draws on primary research undertaken in the North East of England (NE) to explore the importance of private transport in allowing wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 11 publications
2
32
0
6
Order By: Relevance
“…The car seems to be a great helper in reaching the necessary flexibility to live a modern and fruitful life, as noted in studies on the role of women (Craig, 2005;Dobbs, 2006Dobbs, , 2007Heine and Mantz, 1999;Skinner, 2003;Schwanen, 2007b) and on time scarcity (Gershuny, 2005;Hjortol, 2005;Skinner, 2005;Southerton, 2003).…”
Section: Understanding Car Mobility Patterns and Choicesmentioning
confidence: 98%
“…The car seems to be a great helper in reaching the necessary flexibility to live a modern and fruitful life, as noted in studies on the role of women (Craig, 2005;Dobbs, 2006Dobbs, , 2007Heine and Mantz, 1999;Skinner, 2003;Schwanen, 2007b) and on time scarcity (Gershuny, 2005;Hjortol, 2005;Skinner, 2005;Southerton, 2003).…”
Section: Understanding Car Mobility Patterns and Choicesmentioning
confidence: 98%
“…Studies show that females make fewer trips, work closer to their homes, and are more dependent on public transport than men (Hanson and Hanson, 1980;Rosenbloom, 2004). Women are also more likely to engage in non-work travel with complex trip structures (Dobbs, 2005). Other studies have also reported a slow but gradual convergence in gender mobility differences in developed countries (Crane, 2007).…”
Section: Gender and Mobilitymentioning
confidence: 98%
“…Many studies show that mobility could be an enabler for women to have better access to economic opportunities (e.g., Dobbs, 2005;Porter, 2008). There is also significant evidence on how constrained mobility and accessibility narrow down the opportunities for women's economic empowerment (Uteng, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%